The Effect of Screen Hole Diameter and Hammer Tip Speed on the Subsequent Particle Size of Ground Corn Analyzed With and Without Sieving Agent - Caitlin E. Evans; Haley K. Wecker; Nelsa M. Beckman; Marut Saensukjaroenphon; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Reducing the particle size of grains increases the ratio of surface area to volume which provides digestive enzymes greater access to nutrients, therefore improving utilization of the feed. Hammermills are a very cost-effective method of reducing grains to very fine particle sizes for feeding. A variety of settings can be changed on hammermills to achieve a target particle size. Thus, the objective of this experiment was to determine the effects of screen hole diameter, hammer tip speed, and the inclusion of a sieving agent on the particle size of corn. Treatments were arranged in a 4 × 6 × 2 factorial with screen hole diameter (10/64, 12/64, 16/64, 24/64 in.), hammer tip speed (20,500, 18,450, 16,400, 14,350, 12,300, and 10,250 ft/min), and particle size analytical method (with and without sieving agent). All treatments were ground using a Bliss Hammermill (Model 22115) equipped with a variable frequency drive (VFD) and a 25 HP motor. The screen hole diameter and hammer tip speed were randomized to reduce the effects of grinding and sampling order. There were 3 replicates per treatment. Samples were analyzed for geometric mean diameter (dgw) and standard deviation (Sgw) of the particle size. There was no evidence of a screen hole diameter × hammer tip speed × sieving agent interaction for all variables (P>0.327). There was a linear screen hole diameter × linear hammer tip speed interaction (P<0.001) for dgw. When increasing tip speed from 10,250 to 20,500 ft/min, the rate of decrease in dgwwas greater as screen hole diameter increased from 10/64 to 24/64. There was a quadratic screen hole diameter × linear hammer tip speed interaction (P<0.035) for Sgw. When increasing the screen size from 10/64 to 24/64, the rate of increase in Sgwwas greater as tip speed increased from 10,250 to 16,400 ft/min and was similar from 16,400 to 20,500 ft/min. There was no evidence of a screen hole diameter × hammer tip speed interaction for percent fines (P>0.153). There was no evidence of a screen hole diameter × sieving agent or hammer tip speed × sieving agent interaction for dgwor Sgw(P>0.540). There was a linear screen hole diameter × sieving agent interaction (P<0.001) for percent fines. When increasing the screen size from 10/64 to 24/64, the rate of decrease in percent of fine particles was greater when sieving agent was used compared to when it wasn’t used. The results of this trial indicate that the particle size range for a specified hammermill screen size can be altered by adjusting the hammer tip speed with a VFD. Additionally, particle size should be determined with the addition of sieving agent during analysis to more accurately characterize the particle size distribution, especially of finer particles that may influence flowability or animal intake.
Keywords: hammer tip speed; particle size; screen hole diameter; and sieving agent